Pengaruh Persepsi Akuntabilitas, Kompetensi, Profesionalisme, Integritas dan Objektivitas Terhadap Persepsi Kualitas Audit - Astri Anggraini; Dedy Djefris; Anda Dwi Haryadi (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2023)
This study aims to determine the influence of perceptions of accountability, competence, professionalism, integrity, and objectivity on the perception of audit quality, while the variables used in the research are accountability, competence, professionalism, integrity, and objectivity as independent variables, while audit quality as dependent variables. The population in this study were auditors working at a Public Accounting Firm in the South Jakarta area, data collection using primary data and sampling was carried out using the purposive sampling method with the number of samples obtained as many as 98 respondents. Data collection is carried out by distributing questionnaires through a google form which is intended to be filled out by auditors working at a Public Accounting Firm in the South Jakarta area. Data processing using SPSS V.25 software. The results of this study show that the auditor accountability variable has no influence on the quality of the audit, while the variables of auditor competence, auditor professionalism, auditor integrity and auditor objectivity have an influence on audit quality.